1979
DOI: 10.1093/ije/8.4.339
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Respiratory Illness in Primary Schoolchildren and the Use of Gas for Cooking

Abstract: The study was designed to determine whether there was an association between indoor levels of nitrogen dioxide (NO2) and respiratory illness and lung function in schoolchildren. NO2 was measured for one week in the winter outside and inside the homes of children aged 6-7 years living and attending primary schools in a defined 4 square km area in Middlesbrough, Cleveland, UK. Outdoor levels of NO2 measured at 75 points within the area ranged from 14-24 ppb weekly average. Measurements were also made in 428 kitc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

1983
1983
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 0 publications
1
35
0
1
Order By: Relevance
“…They may be more susceptible to indoor environmental pollutants than adults, and the proportion of their time indoors is likely to be greater. Children may also be examined readily in large numbers through the schools.Indoor environmental factors that have received the most attention in the past are environmental tobacco smoke (Schenker et al, 1983;Charlton, 1984;Ware et al, 1984;Somerville et al, 1988;Chinn and Rona, 1991;Forastiere et al, 1992;Guneser et al, 1994;Goren and Hellmann, 1996) and directly or indirectly measured nitrogen dioxide, mainly from gas cooking appliances (Melia et al, 1979;Goldstein et al, 1979;Ware et al, 1984;Ogston et al, 1985;Neas et al, 1991). However, there are no data available concerning the investigations of the effects of indoor environment on the respiratory health of school children in a subtropical region.…”
mentioning
confidence: 99%
“…They may be more susceptible to indoor environmental pollutants than adults, and the proportion of their time indoors is likely to be greater. Children may also be examined readily in large numbers through the schools.Indoor environmental factors that have received the most attention in the past are environmental tobacco smoke (Schenker et al, 1983;Charlton, 1984;Ware et al, 1984;Somerville et al, 1988;Chinn and Rona, 1991;Forastiere et al, 1992;Guneser et al, 1994;Goren and Hellmann, 1996) and directly or indirectly measured nitrogen dioxide, mainly from gas cooking appliances (Melia et al, 1979;Goldstein et al, 1979;Ware et al, 1984;Ogston et al, 1985;Neas et al, 1991). However, there are no data available concerning the investigations of the effects of indoor environment on the respiratory health of school children in a subtropical region.…”
mentioning
confidence: 99%
“…Passive smoking has not previously been reported to increase personal NO2 exposure, but the finding seems reliable because several studies have shown that smoking increases indoor NO2 concentrations (39,(42)(43)(44).…”
Section: Discussionmentioning
confidence: 89%
“…First, most of the effect of gas appliances was included via the effect of the NO2 concentration in the bedroom; removing the bedroom concentration from the regression model decreased the pvalue for gas appliances to <0.0001. Second, the highest NO2 concentrations have been reported from gas stoves with continuously burning pilot lights (28,39,40), which are rarely used in Denmark. Third, in contrast to most previous studies, we dealt only with children who might be expected to be less exposed than adults because 1) NO2 concentrations in the kitchens and living rooms of houses with gas stoves decrease with decreasing height (41) and 2) children spend less of the time than their mothers do in the kitchen (36).…”
Section: Discussionmentioning
confidence: 99%
“…This source influence on NO2 has also been reported previously. 12 ' 13 The effects of both of these characteristics were included in the model by the use of four different regression relationships for the four possible combinations of cooking fuel (gas/ electric) and smoking (smoker/no smoker), as shown in Table I. These detrended regression coefficients were then used with indoor hour-specific means determined separately for each of the cooking/smoking subcategories (see Table I) along with the fixed site monitoring data in order to estimate indoor concentrations of nitrogen dioxide for the homes of all study subjects.…”
Section: Exposure Modelmentioning
confidence: 99%